(untitled) (Sciences & Technologie. C, Biotechnologies, 2006)
The West coast of Béjaia has 60 km of meadows. The observations carried out on the sea birds during four years, 1999, 2000, 2001and 2002, revealed ninespecies. Two are regarded as pelagic, Calonectris diomedeaand Morus bassanus. The seven others are rather coastal species. These were of Phalacrocorax carbo, Phalacrocorax aristotelis, Larus ridibundus, Larus fuscus, Larus michahellis, Sterna sandvicensis and Sterna hirundo. Larus cachinnansis regarded as the only nesting species in this area, its current number is estimated at 810 pairs. The population of the Yellow legged gulls multiplied seven times since 1978.